Management strategies for recurrent acute rhinosinusitis. Issue 4 (10th July 2019) - Lin, Jiahui; Kacker, Ashutosh
Abstract : Background: Management of patients with recurrent acute rhinosinusitis (RARS) is often challenging, and robust data in the literature is scant. The aim of this study is to better characterize the current treatment strategies for RARS used by otolaryngologists. Methods: An online survey sent to all members of the American Rhinologic Society in a 1 month period evaluated demographics, practice characteristics, and management strategies for patients with RARS, subdivided into those with (RARSwD) and without (RARSsD) septal deviation. Eighty‐eight practicing members responded, of whom 41% were fellowship‐trained rhinologists. Results: For most cases of RARSsD, 61% of otolaryngologists would primarily use medical management. Most would wait until patients had experienced 4–5 episodes to perform balloon sinuplasty (80%) or formal sinus surgery (79%). The sinus surgery procedure of choice was limited sinus surgery (62%). For RARSwD, 52% primarily chose medical management. Most would wait until patients had experienced 4–5 episodes to perform balloon sinuplasty (80%) or formal sinus surgery (78%). Nearly all fellowship‐trained rhinologists (97%) would perform limited sinus surgery with septoplasty for RARSwD, compared to only 70% of other otolaryngologists who would do so and 24% who would perform complete sinus surgery with septoplasty. While 89% of practitioners in private practice would wait to perform balloon sinuplasty until patients had experienced 4–5 episodes, only 68% of those in academia would wait this long and 23% would do so after only 1–3 episodes. Conclusions: Treatment of patients with RARS is complex, and the differences in strategies employed between groups of otolaryngologists may reflect their training backgrounds and different patient populations. Level of Evidence: V